WORKSHOP ON MAKING DOUGHNUT WITH THE ADDITION OF VEGETABLES AND FRUITS EXTRACT TO KASIH SAYANG PAUD STUDENT’S MOTHERS - Hairuddin, Abduh (Journal of Saintech Transfer, 2021)
The prevalence of deficiency of vegetables and fruit consumption in Indonesia among children < 10 years is 93.6%. Donuts are snacks that also have some good nutritional content. The purpose of this community dedication is to increase the knowledge of parents, especially mothers of students in PAUD, about the benefits of vegetables and fruit. Improve skills in making donuts with a combination of vegetables and fruits juices to increase vegetables and fruits intake in preschool age children. The service was carried out at Kasih Sayang PAUD, the form of activity was counseling for 45 minutes and continued with training on making donuts with the addition of juice (green spinach, carrots, dragon fruit and chopped red spinach). The results of the training activities showed an increase in participants' knowledge from an average of 6.2 points before training to 8.27 points after training. Participants are also proficient in making donuts with the addition of vegetable and fruit juices.